The Effectiveness of Integrating Scientific Nutrition Education into Physical Education on Nutrition Knowledge and Healthy Behavior Intentions among Junior High School Students - Zhao Shuai; Ni Nyoman Parwati; I Gde Wawan Sudatha (Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the effectiveness of an experimental approach integrating scientific nutrition education into physical education learning in improving nutrition knowledge and healthy behavior intentions among junior high school students. The study used a quasi-experimental design with a pretest–posttest control group model, involving 40 seventh-grade students at Beijing No. 3 Middle School (Xicheng District, Beijing, China) who were divided into an experimental group and a control group through class-based randomization. The experimental group followed an integrated